TURKIC-LANGUAGE LITERATURE IN IRAN: A CASE STUDY FROM THE 17TH CENTURY - Zavqiyjon Qobiljon o‘g‘li Fayzullayev (Frontline Social Sciences and History Journal, 2024)
In this article, thoughts are expressed regarding the Turkish-speaking literary atmosphere in the 17th century in the world, particularly, in Iran, and brief information is given about some of the authors of the period.